Disfunción familiar y rendimiento académico del área de comunicación en estudiantes de la institución educativa N° 601529 de la comunidad nativa Nuevo Porvenir Pastaza, Iquitos 2024 - Del Aguila Gallardo, Victoria Mirza (2025)
This research sought to determine how family dysfunction is related to academic performance in communication. This is a quantitative study of the descriptive correlational type, with a non-experimental design. The population consisted of 35 elementary school students. The study considered 100% of the population as a sample and used surveys and questionnaires to collect information. The findings revealed a significant and direct relationship between family dysfunction and academic performance in communication, with a moderate correlation (Pearson: 0.575), confirming the study hypothesis.